Jesus’ Itineraries in the Light of GIS Research: Three Case Studies - Marciak, Michał; Sobczyński, Daniel; Szypuła, Bartłomiej; Abadi, Omri; Mróz, Konrad (The Biblical Annals, 2025)
This paper discusses select itineraries known from the Gospels using the tools of Geographic Information Systems and satellite archaeology. As a result, several conclusions on the geohistorical and sociohistorical context are suggested. First, the Roman imperial road from Jericho to Jerusalem covered an earlier ancient road; given the road’s length (29 km) and inclination (6.9 degrees), it entailed a 9-hour travel route unlikely to be undertaken on foot within one day. Second, it appears that travellers between Kh. Qana and Capernaum had two good options for one-day travel in Early Roman times – a topographic route via the valley of Nahal Tsalmon (28 km/7 hours) or a route via the Arbel Valley (30 km/8 hours). Third, the most probable direct route from the Hajlah ford to Kh. Qana led via the vicinity of the Nazareth Range. The travel distance between the Hajlah ford and Kh. Qana amounts to at least 130 km and as such requires five or six full days of travel on foot. Fourth, as for the routes from the northern identifications of the baptism site (Yardenit, Gesher, Makhadet Abara) to Kh. Qana, travel only from Yardenit may be achieved within one long travel day (40 km).